SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN DAN PASAR - Safitri, Dian Anggraeni; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of the disclosure of sustainability report to the financial performance and market. The objects of the research are 10 companies which have published the sustainability report and incorporated in the IDX (Indonesia Stock Exchange) in 2011-2013 periods. The sample collection technique has been done by using purposive sampling method. The dependent variable is financial performance which is measured by using return on asset (ROA) and current ratio, as well as market performance which is measured by using Tobinâs Q. meanwhile, the independent variable is the SRDI. The data analysis technique has been done by using descriptive analysis technique; the hypothesis test has been done by using the manova. Based on the result of Between-Subject Effect test, the first hypothesis states that the disclosure of sustainability report has positive influence to the financial performance is accepted by its significance 0.049 on the proxy of return on asset (ROA), and 0.043 on the proxy of current ratio, the second hypothesis states that the disclosure of sustainability report has positive influence to the performance of market is accepted with its significance 0.046. Â Keywords:Â  Â Â Â Â Â  Sustainability Report, Financial Performance, Market PerformanceÂ